Appraisal of hydro-ecology, geomorphology, and sediment behavior during low and high floods in the Lower Indus River Estuary. Issue 2 (6th January 2022) - Boota, Muhammad Waseem; Yan, Chaode; Soomro, Shan-e-hyder; Li, Ziwei; Zohaib, Muhammad; Ijaz, Muhammad Wajid; Yousaf, Ayesha; Zafar, Muhammad Awais
Abstract: The riverine ecosystem is reliant on freshwater; however, morphological changes and sediment load destabilize the natural river system which deteriorates the ecology and geomorphology of the river ecosystem. The Lower Indus River Estuary (LIRE) geomorphological response was synthesized using satellite imagery (1986–2020) and evaluated against the field measurements. The estuary sinuosity index has an increasing trend from 1.84 (1986) to 1.92 (2020) and the estuary water area is increased from 101.41 km 2 (1986) to 110.24 km 2 (2020). The sediment load investigation at Kotri barrage indicated that the median size of bed material samples during the low-flow period falls between 0.100 and 0.203 mm and the bed material after the high flow has clay and silt (<0.0623 mm) ranging from 17–95% of the total weight of samples. The vegetated land loss on the banks is positively correlated with the peak runoff at Kotri barrage ( r 2 =0.92). The bank erosion was computed with high precision ( r 2 =0.84) based on an improved connection of the coefficient of erodibility and excess shear stress technique. This study will be helpful for policymakers to estimate the ecological health of LIRE, and sediment fluxes play an essential role in the mega-delta system and coastal management. HIGHLIGHTS: Remote sensing trajectory analysis of channel migration in the Lower Indus River Estuary from 1986 to 2020. Hydro-geomorphological response based on the analysis of several channel morphometric parameters. Estimation of sediment load, erosion, and deposition during low and high flood periods.